MO171: Chronic Inflammation Might Protect Haemodialysis Patients from Severe COVID-19. (3rd May 2022) - Prietl, Barbara; Odler, Balazs; Kirsch, Alexander H; Artinger, Katharina; Eigner, Manfred; Schmaldienst, Sabine; Pfeifer, Verena; Stanzer, Stefanie; Eberl, Anita; Raml, Reingard; Rosenkranz, Alexander; Brodmann, Marianne; et al.
Abstract: BACKGROUND AND AIMS: Patients on haemodialysis (HD) are expected to have excess mortality in coronavirus disease 2019 (COVID-19). This was challenged by a recent study reporting HD patients to have comparable mortality and decreased ICU admissions when hospitalized with COVID-19. It was speculated that an altered immune system due to chronic inflammation might protect HD patients from severe COVID-19. Therefore, we designed a study to describe the peripheral blood immune phenotype in HD patients and respective controls with COVID-19. METHOD: Sixty-four patients (31 HD, 33 non-HD) with PCR-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and 16 control patients (10 HD, 6 non-HD) were prospectively included. According to symptoms, COVID-19 patients were categorized as asymptomatic/mild and moderate/severe COVID-19 phenotypes. Cytokine profiling and immune phenotyping were performed. RESULTS: Th1 and Th17 plasma cytokine levels were highly increased in HD patients without SARS-CoV-2 infection and were not significantly regulated during COVID-19. In non-HD COVID-19 patients, these cytokines increased significantly with disease severity. While all patients with moderate/severe COVID-19 showed hallmarks of COVID-19 such as decreased CD3 + CD4 + and CD8 + and CD4 + CD25 hi FoxP3 + regulatory T cells, significantly increased CD38 + CD8 + effector memory and CD38 + CD8 + TEMRA T cells were detected in HD compared to non-HD patients with moderate/severe COVID-19. Furthermore, CD161 + CD8 + T cells decreased significantly in non-HD COVID-19 patients dependent on disease severity, but not in HD patients. Dynamics of B cells and subtypes were comparable in HD and non-HD COVID-19 patients. Significantly fewer moderate/severe COVID-19 HD patients needed ICU treatment [1/13 (7.7%) HD, 12/24 (50%) non-HD], whereas no difference in mortality was observed [4/31 (12.9%) HD, 6/33 non-HD (18.2%)]. CONCLUSION: HD patients might be protected from severe COVID-19 due to their chronic inflammatory state with increased CD38 + CD8 + effector memory and TEMRA T cells as well as CD161 + CD8 + T cells.